Biogeography, Speciation and Taxonomy within the genus Bactrocera Macquart with application to the Bactrocera dorsalis (Hendel) complex of fruit flies (Diptera: Tephritidae: Dacinae) - Drew, R.a.i.; Hancock, D.l. (Zootaxa, 2022)
The genus Bactrocera Macquart comprises a large group of some 750 species distributed across the Asia-Pacific and Afrotropical regions. Most of these have been described and revised by Drew (1989), Drew & Hancock (1994) and Drew & Romig (2013, 2022). A taxonomic study of such a large and diverse group of species provides valuable information that can be used in the elucidation of concepts on biogeography and evolution that are presented in this paper. While a wider discussion of this genus and its many complexes of sibling species awaits a future publication, in this paper we discuss the Bactrocera dorsalis (Hendel) complex in light of current knowledge of biogeography and evolution in the Asia-Pacific region. Within the dorsalis complex, 70 species were recognized in South-East Asia by Drew & Romig (2013) and eight listed for Papua New Guinea and Australia by Drew (1989). Seventy-nine species are now included in this paper. Within this complex, two major groups occur, one with species responding to methyl eugenol and the other to cue lure. The 34 non-cue lure responding group of species are discussed, most of which respond to methyl eugenol and seven of which are recognized as having pest status, namely, B. carambolae Drew & Hancock, B. caryeae (Kapoor), B. dorsalis (Hendel), B. kandiensis Drew & Hancock, B. occipitalis (Bezzi), B. ochroma Drew & Romig and B. papayae Drew & Hancock. An eighth species, Bactrocera invadens Drew, Tsuruta & White is included in this discussion on the basis of its molecular similarity to B. dorsalis. The remaining group of 45 species, mostly cue lure-responding and including the pest species B. pyrifoliae Drew & Hancock and B. syzygii White & Tsuruta, are also discussed. Morphological and ecological data are presented for each pest species and their biosecurity risks assessed. In addition, new data based on further research on the male aedeagus have demonstrated that B. carambolae, B. occipitalis, B. papayae and B. invadens are markedly different from B. dorsalis in the dimensions and shape of the glans and preglans appendix. Based on this evidence, and that presented by Drew & Romig (2016), the withdrawal of B. papayae and B. invadens from synonymy with B. dorsalis by Drew & Romig (2016) remains valid, while the similarity in aedeagus characters between B. papayae and B. philippinensis further supports the synonymisation of these two species. The remainder of the 34 non-cue lure responding species are distributed from the Indian subcontinent, across South-East Asia, Papua New Guinea and north-eastern Australia, some with restricted geographic distributions and specific host plant species. Comments on the reliability of molecular phylogenies in the Dacini are included, with the published mitogenome of ‘Dacus longicornis’ regarded, on morphological evidence, as data based on a misidentification of Dacus (Mellesis) polistiformis (Senior-White), and the recent synonymy of B. albistrigata (de Meijere) with B. frauenfeldi (Schiner) considered to be based on insufficient evidence.